The Relationship Between Family History and Smoking Behavior of Family Members - Putri, Okky Oktaviyana; Susanto, Tantut; Susumaningrum, Latifa Aini (Journal of Rural Community Nursing Practice, 2023)
Smoking is often found in various environments, especially in the family environment. Various efforts or programs that have been echoed and implemented to overcome these problems include the Healthy Indonesia Program with a Family Approach (PIS-PK). This study aimed to analyze the relationship between family health history and the smoking behavior of family members. The research design is correlational with a cross-sectional approach. The population in this study were all families in the working area of the Kaliwates Health Center, Jember Regency, totaling 12,840 families, with a sample of 170 respondents. The sampling technique used was multistage sampling with the data collection tools, namely the family health history questionnaire and the GN-SBQ smoking behavior questionnaire. The results of this study indicate that the Chi-Square statistical test obtained a p-value of 0.615 (<0.05) where there is no relationship between family health history and the smoking behavior of family members in the working area of the Kaliwates Health Center. In this study, most family health history was in good health, as seen from the history data (65.9%). However, most of the families in the working area of the Kaliwates Health Center showed smoking behavior in the very severe category (60.6%). This study concludes that no significant relationship exists between family health history and smoking behavior. It is hoped that with this research, health workers can help improve counseling related to smoking behavior in the working area of the Kaliwates Health Center.